2022
DOI: 10.1093/mnras/stac1526
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale expansion of OB stars in Cygnus

Abstract: The proper motions (PMs) of OB stars in Cygnus have recently been found to exhibit two large-scale kinematic patterns suggestive of expansion. We perform a 3D traceback on these OB stars, the newly-identified OB associations and related open clusters in the region. We find that there are two groups of stars, associations and clusters and that they were each more compact in the past, reaching their closest approach $7.9^{+3.0}_{-1.8}$ and $8.5^{+0.8}_{-2.8}$ Myr ago. We consider two main scenarios for the drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The Cygnus region observed in this work is known to harbor many sites of star formation, including extensive OB associations (Comerón & Pasquali 2012;Berlanas et al 2019;Quintana & Wright 2021;Orellana et al 2021;Quintana & Wright 2022), Wolf-Rayet (W-R) stars (Koch-Miramond et al 2002;Rauw et al 2015), and H II regions (Beerer et al 2010;Emig et al 2022). As such, it has been invaluable for studying the entire life cycle of stars-many of which have formed within the past few million years (van der Walt et al 2021;Beuther et al 2022).…”
Section: Survey Motivation and Overviewmentioning
confidence: 95%
See 1 more Smart Citation
“…The Cygnus region observed in this work is known to harbor many sites of star formation, including extensive OB associations (Comerón & Pasquali 2012;Berlanas et al 2019;Quintana & Wright 2021;Orellana et al 2021;Quintana & Wright 2022), Wolf-Rayet (W-R) stars (Koch-Miramond et al 2002;Rauw et al 2015), and H II regions (Beerer et al 2010;Emig et al 2022). As such, it has been invaluable for studying the entire life cycle of stars-many of which have formed within the past few million years (van der Walt et al 2021;Beuther et al 2022).…”
Section: Survey Motivation and Overviewmentioning
confidence: 95%
“…Also notable in that sample is the difference in distances for J2021+3651 (discussed in Hessels et al 2004) and J2032+4127 (0.5 kpc) compared to the difference in their DMs (253 pc cm −3 ). Gaia observations have been used to find clusters of dusty OB regions at distances ; 1.4 kpc (Orellana et al 2021;Quintana & Wright 2022), which may support a complex line-of-sight dependence for DM.…”
Section: Cygnus Pulsar Populationmentioning
confidence: 99%
“…Kroupa et al (2001) postulated that OB associations are the expanded remnants of compact star clusters, whereas other authors have shown that the kinematics of these regions suggests that they were never more dense in the past (Wright et al 2014;Wright et al 2016;Ward & Kruijssen 2018). More recent work, however, has shown evidence of expansion in other regions (Kounkel et al 2018;Quintana & Wright 2022), which has been attributed to feedback.…”
Section: Methodsmentioning
confidence: 99%
“…With the exception of some extremely high-velocity stars (10-10 2 km s −1 ) ejected from n-body (n 3) interactions (Ducourant et al 2017;Fernandes et al 2019;Bally et al 2020;Rivera-Ortiz et al 2021), the stellar motions could also be affected by their dense-gas structures. Young stars could directly inherit the turbulent field of the gas structure (Ha et al 2021;Krolikowski et al 2021;Gupta & Chen 2022;Quintana & Wright 2022) and obtain further acceleration due to the gravitational instability or other interactions among the parental filaments or clumps (Stutz & Gould 2016;Getman et al 2019;Kim et al 2019;Zamora-Avilés et al 2019;Sharma et al 2020;Álvarez-Gutiérrez et al 2021). Stutz & Gould (2016) proposed one particular scenario where the filament in Orion A could have an oscillation that drives the young stars toward transverse directions, eventually forming a broadened stellar distribution in parallel with the filament.…”
Section: Introductionmentioning
confidence: 99%